The Role of HIV Infection in the Pathophysiology of Gestational Diabetes Mellitus and Hypertensive Disorders of Pregnancy - Phoswa, Wendy N. (Frontiers in Cardiovascular Medicine, 2021)
Purpose of the review: The main objective of this study is to investigate mechanisms associated with gestational diabetes mellitus (GDM) and hypertensive disorders of pregnancy (HDP) in HIV infected pregnant women by looking how placental hormones such as (progesterone and prolactin) and basic haemostatic parameters are regulated in HIV infected pregnancies. Recent findings: HIV/AIDS are a major global obstetric health burden that lead to increased rate of morbidity and mortality. HIV/AIDS has been associated with the pathophysiology of GDM and HDP. Increased risk of GDM due to highly active antiretroviral therapy (HAART) usage has been reported in HIV infected pregnancies, which causes insulin resistance in both pregnant and non-pregnant individuals. HAART is a medication used for lowering maternal antepartum viral load and pre-exposure and post-exposure prophylaxis of the infant. In pregnant women, HAART induces diabetogenic effect by causing dysregulation of placental hormones such as (progesterone and prolactin) and predispose HIV infected women to GDM. In addition to HIV/AIDS and GDM, Studies have indicated that HIV infection causes haemostatic abnormalities such as haematological disorder, deregulated haematopoiesis process and the coagulation process which results in HDP. Summary: This study will help on improving therapeutic management and understanding of the pathophysiology of GDM and HDP in the absence as well as in the presence of HIV infection by reviewing studies reporting on these mechanisms.